2018
DOI: 10.3390/lubricants6010002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Texturing on Cast Iron Reciprocating against Steel under Cyclic Loading in Boundary and Mixed Lubrication Conditions

Abstract: This study investigates the effect of laser surface texturing on the friction behavior of grey cast iron reciprocating under boundary, mixed lubrication conditions and cyclic loading. Four geometrical parameters of micro-textures (feature depth, feature diameter, area fraction, and sliding direction) were studied using a design of experiments (DoE) approach. The results showed that depending on the geometry, micro-textures can have either a positive or a negative effect on the friction behavior. The DoE analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies by Podgornik and Sedlacek et al [17][18][19] on rough surfaces showed that the beneficial effects of textures can be affected by skewness and kurtosis parameters. Meylan et al [20] tested different textures on rough surfaces and found that most of the textures had similar or worse tribological properties than those of the untextured references. This suggests that the frictional behavior of textured rough surfaces remains to be investigated and that their friction mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Podgornik and Sedlacek et al [17][18][19] on rough surfaces showed that the beneficial effects of textures can be affected by skewness and kurtosis parameters. Meylan et al [20] tested different textures on rough surfaces and found that most of the textures had similar or worse tribological properties than those of the untextured references. This suggests that the frictional behavior of textured rough surfaces remains to be investigated and that their friction mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The textured surface showed a larger reduction in friction (up to 60%) and wear (higher than 80%) compared the untextured sample. Nevertheless, Meylan et al [38] investigated the effect of the geometrical parameters of micro-textures on cast iron reciprocating against steel. The dimple depth and diameter were the most significant factors.…”
Section: Introductionmentioning
confidence: 99%